Rancang Bangun Trainer Air Conditioning Jenis Split Untuk Media Pembelajaran: Rancang Bangun Trainer Air Conditioning Jenis Split Untuk Media Pembelajaran - Ardiansyah, Achmad (Jurnal Rekayasa Mesin, 2020)
One of the supporting factors for comfort in activities in the room is the installation of air conditioning as air conditioning. Air Conditioning (AC) is an equipment used to condition the air so that it can reach the appropriate temperature and humidity according to comfortable air conditions. So as to provide work comfort for people who carry out certain activities in the room.The principle of air cooling in air conditioning involves the refrigeration cycle, which is the air is cooled by the refrigerant (freon), then the freon is pressed using a compressor until a certain pressure and the temperature rises, then it is cooled by environmental air so that it melts. The process mentioned above runs repeatedly so that it becomes a cycle called the cooling cycle in the air which functions to take heat from the air and release this heat outside the room.The expected results of the design of the trainer air conditioner design can meet the aspects of effectiveness to be achieved, namely aspects of regulations / provisions, aspects of functions / tasks, aspects of plans / programs, aspects of goals / ideal conditions.Based on the table of general construction steel according to DIN 17100 (Sept. 1966) in terms of the tensile stress of the frame material (fmax) St 37 - 2 = 37.18 Kg / mm2 or 364.36 N / mm2, with the safety factor (Sf) = 2, and the allowable tensile stress (fci) = fmax: Sf = 182.18 N / mm2, because the bending stress is 14.08 N / mm2, the calculation result is smaller than the allowable tensile stress of the material which is 182.18 N / mm2, the strength of the frame used is SAFE. Keywords: AC Trainer, AC working principle, Frame strength